Hypoxia‐induced pulmonary hypertension upregulates eNOS and TGF‐β contributing to sex‐linked differences in BMPR2+/R899X mutant mice. (5th December 2022) - Erewele, Ejehi O.; Castellon, Maricela; Loya, Omar; Marshboom, Glenn; Schwartz, Andrew; Yerlioglu, Kayla; Callahan, Christopher; Chen, Jiwang; Minshall, Richard D.; Oliveira, Suellen D.
Abstract: Dysfunctional bone morphogenetic protein receptor 2 (BMPR2) and endothelial nitric oxide synthase (eNOS) have been largely implicated in the pathogenesis of pulmonary arterial hypertension (PAH); a life‐threatening cardiopulmonary disease. Although the incident of PAH is about three times higher in females, males with PAH usually have a worse prognosis, which seems to be dependent on estrogen‐associated cardiac and vascular protection. Here, we evaluated whether hypoxia‐induced pulmonary hypertension (PH) in humanized BMPR2 +/R899X loss‐of‐function mutant mice contributes to sex‐associated differences observed in PAH by altering eNOS expression and inducing expansion of hyperactivated TGF‐β‐producing pulmonary myofibroblasts. To test this hypothesis, male and female wild‐type (WT) and BMPR2 +/R899X mutant mice were kept under hypoxic or normoxic conditions for 4 weeks, and then right ventricular systolic pressure (RVSP) and right ventricular hypertrophy (RVH) were measured. Chronic hypoxia exposure elevated RVSP, inducing RVH in both groups, with a greater effect in BMPR2 +/R899X female mice. Lung histology revealed no differences in vessel thickness/area between sexes, suggesting RVSP differences in this model are unlikely to be in response to sex‐dependent vascular narrowing. On the other hand, hypoxia exposure increased vascular collagen deposition, the number of TGF‐β‐associated α‐SMA‐positive microvessels, and eNOS expression, whereas it also reduced caveolin‐1 expression in the lungs of BMPR2 +/R899X females compared to males. Taken together, this brief report reveals elevated myofibroblast‐derived TGF‐β and eNOS‐derived oxidants contribute to pulmonary microvascular muscularization and sex‐linked differences in incidence, severity, and outcome of PAH.